Amulet. Book six, Escape from Lucien - Kibuishi, Kazu, 1978- (New York : Graphix, 2014)
Navin and his classmates journey to Lucien, a city ravaged by war and plagued by mysterious creatures, where they search for a beacon essential to their fight against the Elf King. Meanwhile, Emily heads back into the Void with Max, one of the Elf King's loyal followers, where she learns his darkest secrets. The stakes, for both Emily and Navin, are higher than ever.
GN390L
Decoding demand: 91 (very high) Semantic demand: 100 (very high) Syntactic demand: 60 (medium) Structure demand: 88 (very high)
Accelerated Reader AR
Keywords: Supernatural -- Comic books, strips, etc; Brothers and sisters -- Comic books, strips, etc; Amulets -- Comic books, strips, etc; Elves -- Comic books, strips, etc; Cartoons and comics; Graphic novels